A Noncontact Skin Oxygen-Saturation Imaging System for Measuring Human Tissue Oxygen Saturation - Hsin-Yi Tsai; Kuo-Cheng Huang; Han-Chao Chang; Yeh, Jer-Liang Andrew; Chung-Hsing Chang (IEEE transactions on instrumentation and measurement, 2014)
The oxygen saturation (SpO 2 ) of human tissue can be measured and the SpO 2 distribution diagram can be built by irradiating the tissue with two wavelengths of light-red (660 nm) and near-infrared [(NIR) 890 nm]. In this paper, two analysis methods are employed to calibrate the measurement accuracy of skin oxygen-saturation imaging (SOSI) system. In addition, to compute the skin tissue oxygen saturation, the partial pressure of oxygen (PaO 2 ) and SpO 2 of nine subjects are measured using transcutaneous oxygen pressure (TcPO 2 ) measurement and SOSI system. The results show the measurement deviation reduced considerably when the center distance between the central region and calculated region is less than 10 mm. Furthermore, the PaO 2 at the interdigital fold between the thumb and the index finger exhibits greater variation (43-61 mmHg), and the converted SpO 2 from TcPO 2 ranges from 78% to 91%. By employing SOSI system, the SpO 2 levels obtained at the dorsum of hand range from 85% to 93%, which is slightly higher (2%-7%) than those measured using TcPO 2 system. This is because: 1) more vessels are located at the region that is measured using SOSI system than that measured using TcPO 2 and 2) more NIR light is absorbed by subcutaneous fat using SOSI system than theoretical simulations. In the future, the SOSI system could provide SpO 2 information to clinicians for diagnosing the health status of patients' cardiovascular system from the variation of SpO 2 distribution diagrams between the tissue and vascular regions, and even in different parts of the human body.